Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Rumah pada PT Baruga Asrinusa Development - Nurul Ramadhani; Andi Mappatompo; Aulia Aulia (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study aims to determine the effect of the marketing mix consisting of product, price, location, and promotion on home purchasing decisions at PT Baruga Asrinusa Development. The background of the study is based on the importance of marketing strategies in the competitive property industry, so companies need to understand the factors that influence consumers before making purchasing decisions. This study uses a quantitative approach with an associative research type. The sample consisted of 190 respondents who were consumers of PT Baruga Asrinusa Development, with an incidental sampling technique. Data were obtained through questionnaires and analyzed using multiple linear regression through SPSS version 25. The results of the study indicate that partially, the variables of product, price, location, and promotion have a positive and significant effect on home purchasing decisions. The coefficient value of each variable is 0.165 for product, 0.180 for price, 0.192 for location, and 0.292 for promotion, where promotion has the greatest influence. In addition, the results of the F test indicate that the four variables simultaneously also have a positive and significant effect. Overall, this study confirms that product development, appropriate pricing, strategic location selection, and effective promotion are marketing strategies that can increase consumer purchasing decisions.